Who is liable for any damage caused to children and adolescents in schools? - Córdova López, Ocner (2018)
In this article, we briefly analyze the civil responsibility that the educational institution must assume regarding the damages suffered by children and adolescents (as students) when they are inside the educational institution or under its authority; we warn that, in spite of existing international and national instruments, such as the Convention on the Rights of the Child of which Peru is a party and the Political Constitution of the State, which establish a duty of the State to provide special protection to children and adolescents, they are suffering damages within educational institutions or under their authority. In our environment, no civil liability has been established against the breach of this duty of protection that causes harm to minors in educational institutions.